Hubungan Pola Asuh Orang Tua dengan Big Five Personality pada Remaja - Hardjanto, Nadhira Nurlathifah; Triman, Arif (Jurnal Online Psikogenesis, 2023)
Personality is one of the development tasks of adolescents that happened during transition to adulthood. One of the popular theories of personality is Big Five Personality. Parenting styles is one of the factors that affect personality on adolescents. This study aims to see the relationship between parenting styles and big five personality in adolescents. This study uses quantitative methods with accidental sampling technique. Total of participants in this study was 202 adolescents. The instrument that used in this study was the Parenting Styles and Dimensions Questionnaire (PSDQ) to measure parenting styles and Big Five Inventory (BFI) to measure big five personality. This study uses the Spearman correlation test technique with the results that authoritative parenting has a positive and significant relationship with openness to experience (0.157 p<0.05), conscientiousness (0.229 p<0.01), extraversion (0.216 p<0.01), and agreeableness (0.203 p<0.01) and had a negative and significant relationship with neuroticism (-0.265 p<0.001). The results of authoritarian parenting have a positive and significant relationship with neuroticism (0.038 p<0.05). This shows that the more parents apply authoritative parenting, the more dominant openness to experience, conscientiousness, extraversion, and agreeableness personality traits on adolescents. On the other hand, the more parents apply authoritarian parenting, the more dominant the neuroticism personality trait is.